The Effect of Project Management Performance on Machine Operational Readiness at PT GPE (Medion Group) - Evan Nugraha; Dodi Rukmana; Oviyan Patra; Hendy Suryana (Journal of Social Research, 2025)
This research aims to analyze the influence of project management on machine operational readiness at PT Gallaria Prospera Eterna (PT GPE). Five variables were examined: integration management, time management, cost management, quality management, and resource management. Previous issues, such as project delays and cost overruns, prompted the need for an evaluation of the project management system. A quantitative method was employed, utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results indicated that integration management (? = 0.245), time management (? = 0.235), and resource management (? = 0.232) had a significant effect on machine operational readiness. Time and resource management also exhibited positive quadratic effects (QE = 0.170 and QE = 0.181), while cost management had a negative quadratic effect (QE = –0.309). Quality management was found to be statistically insignificant. The R² value of 0.689 and Q² value of 0.567 indicate that the model has strong explanatory and predictive power. The implementation of strategies based on these findings—such as establishing a Project Management Office (PMO), digitalizing project tracking, and strengthening human resources—has successfully improved the execution of the second-phase fermenter machine procurement project, delivering it on time, within budget, and fully operational.